Participatory processes for integrated watershed management / (Acc: 1799) - Sharma, Prem N. (Kathmandu, Nepal : Participatory watershed management training in Asia, 1997)
This section starts with the introduction of the regional workshop. Then it makes a brief review of the participatory approaches which are used in some of the Asian countries. Based on the analysis of various case studies (third article) of people's participation in WM and lessons learned, the fourth article culls out the key elements of participatory processes that are considered to be essential for integrated watershed management. The fifth article goes into participatory methods for watershed management.
Keywords: Watershed management